Outcomes of Surgical Repair for Truncus Arteriosus: A 30-Year Single-Center Experience - Yu Ri Lee; Dong-Hee Kim; Eun Seok Choi; Tae-Jin Yun; Chun Soo Park (Journal of Chest Surgery, 2023)
Background: We investigated the long-term outcomes of truncus arteriosus repair at a single institution with a 30-year study period. Methods: Patients who underwent repair of truncus arteriosus between 1993 and 2022 were reviewed retrospectively. Factors associated with early mortality, overall attrition, and reintervention were identified using appropriate statistical methods. Results: In total, 42 patients were enrolled in this study. The median age and weight at repair were 26 days and 3.5 kg, respectively. Thirty patients (71.4%) underwent 1-stage repair. There were 8 early deaths (19%). In the univariable analysis, undergoing surgery before 2011 was associated with early mortality (p=0.031). The overall survival rate at 10 years was 73.8%. In the multivariable analysis, significant truncal valve (TrV) dysfunction (p=0.010), longer cardiopulmonary bypass time (p=0.018), and the earlier era of surgery (p=0.004) were identified as risk factors for overall mortality. During follow-up, 47 reinterventions were required in 27 patients (64.3%). The freedom from all-cause reintervention rate at 10 years was 23.6%. In the multivariable analysis, associated arch obstruction (p<0.001) and significant TrV dysfunction (p=0.011) were identified as risk factors for all-cause reintervention. Arch obstruction (p=0.027) and a number of TrV cusps other than 3 (p=0.014) were identified as risk factors for right ventricle to pulmonary artery (RV-PA) reintervention, and significant TrV dysfunction was identified as a risk factor for TrV reintervention (p=0.002). Conclusion: Despite recent improvements in survival outcomes after repair of truncus arteriosus, RV-PA or TrV reinterventions were required in a significant number of patients during follow-up.